الديمقراطية التشاركية على ضوء الدستور المغربي والقوانين التنظيمية - الصديق، مصطفى (المركز المغربي للدراسات الاستراتيجية والعلاقات الدولية, 2022)
تهدف هذه الدراسة إلى إبراز الآليات التي اعتمدها المشرع المغربي لتحقيق الديمقراطية التشاركية، سواء عن طريق الحوار والتشاور مع السلطات العمومية، أو عن طريق تقديم العرائض والملتمسات، كما تسعى، إلى تسليط الضوء على الإشكاليات، والنواقص القانونية والعملية، التي تعترض تطبيقها على أرض الواقع. وقد خلصت الدراسة، إلى أنه بالرغم من التطور الحاصل على مستوى النص الدستوري والقانوني، فإن هذه الآليات، لم تفلح بعد، في القيام بأدوارها الدستورية، المتمثلة في إعداد وتنفيذ السياسات العمومية، ومراقبة مدى فعاليتها ونجاعتها، خاصة على المستويين التشريعي والتنظيمي، مما يحد من فعاليتها في بلوغ غايات المشرع الدستوري من إقرارها، لذا ينبغي إعادة النظر في بعض مقتضياتها بالتحيين أو التغيير لأجل مسايرة نية المشرع في جعل الفاعل المدني مساهما رئيسيا في صنع القرار العمومي.كما يتعين تحقيق مجموعة من الشروط السياسية والمجتمعية اللازمة لتأمين تطبيق هذه المقتضيات على أرض الواقع. This study aims to highlight the mechanisms adopted by the Moroccan legislator to achieve participatory democracy, whether through dialogue and consultation with public authorities, or by submitting petitions. This study also seeks to shed light on the legal and practical problems that hinder its application in reality The study concluded that, despite the development that took place at the level of the constitutional and legal text, these mechanisms have not yet succeeded in carrying out their constitutional roles of preparing and implementing public policies, and monitoring their effectiveness and efficiency, especially at the legislative and organizational levels, which limits its effectiveness in achieving the goals of the constitutional legislator from its application, so some of is requirements should be reconsidered by updating or changing in order to keep the pace with the legislator’s intentions to make the civil agent a major contributor to public decision-making. As such, a set of political and societal conditions necessary to ensure the application of these requirements in reality.
Keywords: الديمقراطية التشاركية -- السياسات العمومية -- الدستور المغربي